Methods and advances in Semen analysis - Mello Martins, Maria Isabel; De Souza, Fabiana Ferreira [UNESP]; Souza, Anne Kemmer; Morotti, Fábio (My University, 2016)
Sperm fertility is considered one of the main factors for successful breeding of domestic animals, either through natural mating or after using reproductive biotechnologies. Kinetics (motility and sperm trajectory) and the morphological characteristics of spermatozoa evaluation are essential for ejaculate analyses and are correlated with male fertility. Due to technical and scientific progress and the need to ensure the maximum fertility potential of sperm cells, several semen evaluation methods have been established over time. This analysis aims to identify key factors for semen quality, using sperm trial parameters and obtain the most accurate results, which can be correlated with fertility, infertility or subfertility. Subjective semen assessment by optical microscopy was one of first methods to evaluate sperm cells and is still the most commonly used method. However, due to its subjectivity (high variability in results), other methods such as computer-aided semen analysis (CASA) are greatly required. Semen analyses using CASA systems associated with flow cytometry have reduced the subjectivity of evaluations, increasing the safety and speed of obtaining data. In addition, these methods have high potential for clinical applications, mainly due to the significant correlation between sperm motility characteristics and in vitro or in vivo fertilization. However, their use is still limited due to equipment costs, data validation requirements, quality control and analysis standardization, especially between laboratories and research centers. Recently, molecular biology studies, such as genomics and proteomics applied to sperm cells and seminal plasma, have also contributed as tools for seminal assessment and identification of breeding males with improved fertility potential. In this context, the aim of this chapter is to provide a practical approach to the main aspects related to different methods of semen analysis applied to domestic animals, in addition to their advantages, disadvantages and the factors that can influence each type of evaluation.
Keywords: CASA; Fertility; Motility; Proteome; Semen analysis